2018
DOI: 10.3390/nano8050347
|View full text |Cite
|
Sign up to set email alerts
|

Loading of Indocyanine Green within Polydopamine-Coated Laponite Nanodisks for Targeted Cancer Photothermal and Photodynamic Therapy

Abstract: The combination of photothermal therapy (PTT) and photodynamic therapy (PDT) in cancer treatment has attracted much attention in recent years. However, developing highly efficient and targeted therapeutic nanoagents for amplifying PTT and PDT treatments remains challenging. In this work, we developed a novel photothermal and photodynamic therapeutic nanoplatform for treatment of cancer cells overexpressing integrin αvβ3 through the coating of polydopamine (PDA) on indocyanine green (ICG)-loaded laponite (LAP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Chen and co-researchers also recorded such increase in size and corresponding decrease in zeta potential after the incorporation of ICG in chitosan NPs in an effort to prepare chitosan-ICG nanospheres. [33] The surface charge of ICG@GC-PP NPs is also comparable with the values that were separately obtained by Li et al [2a] (−37.0 ± 0.8 mV) and Xu et al (−7.33 ± 0.82 mV), [5] for other ICG-based NPs.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Chen and co-researchers also recorded such increase in size and corresponding decrease in zeta potential after the incorporation of ICG in chitosan NPs in an effort to prepare chitosan-ICG nanospheres. [33] The surface charge of ICG@GC-PP NPs is also comparable with the values that were separately obtained by Li et al [2a] (−37.0 ± 0.8 mV) and Xu et al (−7.33 ± 0.82 mV), [5] for other ICG-based NPs.…”
Section: Resultssupporting
confidence: 88%
“…The stretching vibrations at 1475.93 and 1415.81 cm −1 in the ICG@ GC-PP NPs spectrum are attributes of the abounding C=C groups of ICG (originally at 1476.24 and 1420.42 cm −1 , respectively), as also recorded in an earlier study. [5] The above observations and other characteristic peaks for ICG in ICG@GC-PP NPs spectrum at 723.85 and 669.32 cm −1 , confirm the successful synthesis of hybrid ICG@GC-PP NPs.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, it is prone to self-aggregation in aqueous solution, leading to poor uptake by cells. 35,36 Studies have been reported that nanoparticles could enhance drug stability and increase drug accumulation in target cells. Highdose photosensitizer would inhibit the proliferation of neovascular endothelial cells for blocking angiogenesis, and dual-targeted phototherapy could destroy the structure of tumor vessels to enhance drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…PTT makes full use of photothermal agents with strong optical absorption in the near-infrared (NIR) region, which can be activated by using NIR light to kill cancer cells. [25][26][27] Interestingly, indocyanine green (ICG) that is the only contrast agent approved by the United State Food and Drug Administration (U.S. FDA) for clinical applications, has be adopted as a photothermal agent for cancer theranostics due to its attractive light absorption property in the NIR window (700 nm-1000 nm). 28 However, a potential concern on ICG is that it has poor aqueous stability, rapid degradation and fast clearance by the body, which signi¯cantly reduces the e±cacy of PTT.…”
Section: Introductionmentioning
confidence: 99%